CD163+ M2 Macrophages Promote Fibrosis in IgG4‐Related Disease Via Toll‐like Receptor 7/Interleukin‐1 Receptor–Associated Kinase 4/NF‐κB Signaling. Issue 5 (10th April 2022) - Chinju, Akira; Moriyama, Masafumi; Kakizoe‐Ishiguro, Noriko; Chen, Hu; Miyahara, Yuka; Haque, A. S. M. Rafiul; Furusho, Katsuhiro; Sakamoto, Mizuki; Kai, Kazuki; Kibe, Kotono; Hatakeyama‐Furukawa, Sachiko; Ito‐Ohta, Miho; et al.
Abstract : Objective: IgG4‐related disease (IgG4‐RD) is a fibro‐inflammatory condition that can affect multiple organs. We previously demonstrated that TLR7 ‐transgenic C57BL/6 mice showed elevated serum IgG1 levels and inflammation with fibrosis in the salivary glands (SGs), lungs, and pancreas. Moreover, we observed extensive Toll‐like receptor 7 (TLR‐7)–positive CD163+ M2 macrophage infiltration in SGs from IgG4‐RD patients. We undertook this study to examine the fibrotic mechanism via the TLR‐7 pathway. Methods: Gene expression in SGs from human TLR7 ‐transgenic mice and IgG4‐RD patients was analyzed using DNA microarrays. We extracted the common up‐regulated TLR‐7–related genes in SGs from TLR7 ‐transgenic mice and IgG4‐RD patients. Finally, we investigated the interaction between CD163+ M2 macrophages and fibroblasts before and after stimulation with the TLR‐7 agonist loxoribine. Results: In TLR7 ‐transgenic mice and IgG4‐RD patients, IRAK3 and IRAK4 were significantly overexpressed. Real‐time polymerase chain reaction validated the up‐regulation of only IRAK4 in IgG4‐RD patients compared with the other groups ( P  < 0.05). Interleukin‐1 receptor–associated kinase 4 (IRAK4) was strongly detected in and around germinal centers in SGs from patients with IgG4‐related dacryoadenitis and sialadenitis alone. Double immunofluorescence staining showed that IRAK4‐positive cells were mainly colocalized with CD163+ M2 macrophages in SGs ( P  < 0.05). After stimulation with loxoribine, CD163+ M2 macrophages exhibited significantly enhanced expression of IRAK4 and NF‐κB and increased supernatant concentrations of fibrotic cytokines. Finally, we confirmed that the number of fibroblasts was increased by culture with the supernatant of CD163+ M2 macrophages following stimulation with loxoribine ( P  < 0.05). Conclusion: CD163+ M2 macrophages promote fibrosis in IgG4‐RD by increasing the production of fibrotic cytokines via TLR‐7/IRAK4/NF‐κB signaling.